(untitled) (Research, Society and Development, 2021)
Dental anomalies are the result of disorders that occur in the odontogenesis process - responsible for the development of the dental organ. These changes usually occur in the cell formation and differentiation phase. The objective of the present research was to evaluate the prevalence of anomalies of shape and number in orthodontic patients of the Posgraduation Clinic of Universidade Metropolitana de Santos. It was analyzed 262 panoramic radiographs of male and female individuals aged between 06 and 50 years, who underwent or are undergoing orthodontic treatment, adding to the analysis of panoramic radiography and models, the consultation of clinical records. To collect data on dental anomalies, a data spreadsheet was prepared using Microsoft Excel. The statistical test used was Mann-Whitney (p <0.05). A total of 114 dental anomalies were observed, with agenesis being the most frequent anomaly, presenting in 27,86% of patients, with 30% being presented only by third molars. Bullfighting is the second most frequent anomaly presented by 7,25% of the cases, being 47,37% male and 52,63% female. It followed with the supernumeraries affecting 4,20%, presenting more in men (81,8%) than in women (18,2%). Number anomalies were much more prevalent than shape anomalies, with agenesis and taurodontics being the most prevalent among orthodontic patients.